2022
DOI: 10.3846/tede.2022.18090
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure in the Framework of Production Functions: Evidence of Eu Member States at the Regional Level

Abstract: Infrastructure development is seen as an essential tool for boosting economic growth. Infrastructure is funded under various programs to contribute to economic growth, and reduce regional disparities. Evaluations of the results achieved have to be carried out to develop efficient infrastructure development and investment allocation policy. This is highlighted in both the reports of policymakers and scientific publications. The main limitation of these studies is that they focus on assessing the return on infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…b. Infrastructure: The standard of transportation networks, the availability of utilities, and the technological infrastructure derived from published works are examples of indicators (Ferrarez et al, 2020;Mačiulytė-Šniukienė et al, 2022;Savchenko, 2022).…”
Section: Methods a Research Designmentioning
confidence: 99%
See 1 more Smart Citation
“…b. Infrastructure: The standard of transportation networks, the availability of utilities, and the technological infrastructure derived from published works are examples of indicators (Ferrarez et al, 2020;Mačiulytė-Šniukienė et al, 2022;Savchenko, 2022).…”
Section: Methods a Research Designmentioning
confidence: 99%
“…Better infrastructure promotes business growth, lowers transaction costs, and improves accessibility, all of which improve MSME performance. Research has repeatedly demonstrated that infrastructure development and MSME performance are positively correlated, underscoring the need of a favorable physical environment for company success (Cockburn et al, 2013;Fullerton Jr et al, 2013;Hidayat & Prasetyo, 2023;Mačiulytė-Šniukienė et al, 2022). H1: The performance of Indonesian MSMEs is positively and significantly correlated with the quality of the infrastructure (including transportation networks, utility access, and technological infrastructure).…”
Section: Literature Review a Infrastructure And Msme Performancementioning
confidence: 99%
“…Research has indicated a favorable correlation between company performance and transportation infrastructure, with expenditures in this area necessary to maintain growth across several economic sectors, including the agrifood sector (Agnusdei et al, 2022). Furthermore, research has shown that the construction of highways and internet infrastructure has a substantial impact on production results and that infrastructure investments are linked to higher production output when there is less corruption and better government quality (Mačiulytė-Šniukienė et al, 2022). Thus, the body of research supports the idea that infrastructure development is crucial for enhancing the effectiveness of the supply chain and maximizing agricultural productivity (Higgins et al, 2023).…”
Section: Infrastructure Developmentmentioning
confidence: 99%
“…An approach to measure the influence of important variables, such as governmental policies, on healthcare supply chains in emerging nations was put forth (Dixit et al, 2023). Furthermore, (Mačiulytė-Šniukienė et al, 2022) focused on the moderating influence of government quality when examining the economic results of infrastructure development at the regional level. All of these results point to the importance of government policies in fostering infrastructure development and improving supply chain effectiveness in the agriculture industry.…”
Section: Government Policymentioning
confidence: 99%
“…Globally, infrastructure improvement is widely acknowledged as a stimulant for economic expansion. The literature has extensively examined the benefits that well-planned and executed infrastructure projects can have on local and national economies [17]- [19]. Infrastructure investment can lead to higher production, efficiency, and competitiveness for a nation [20].…”
Section: Infrastructure and Economic Growthmentioning
confidence: 99%